Avaliação da aprendizagem no ciclo de alfabetização: o que dizem os Cadernos de Formação do PNAIC? - Oliveira, Gilcéia Damasceno de (2019)
The National Pact for Literacy at the Right Age – Pacto Nacional pela Alfabetização na Idade Certa (PNAIC) is the result of a commitment made between the federal, district, state and municipal governments to ensure the development of literacy of all children at the age recognized as “right”, that is, at eight years old. This dissertation aimed to recognize the proposals for learning assessment for the literacy cycle, conveyed by the PNAIC Training Notebooks (Cadernos de Formação do PNAIC), analyzing what place the student takes on these proposals. To achieve this purpose, we opted for bibliographic research and document analysis. For the analysis of the 19 texts selected from the Pact Notebooks (Cadernos do Pacto) to compose the documentary corpus, we resorted to content analysis. The analytical categories -diagnostic assessment, summative assessment, formative assessment, traditional assessment approach, teacher, student, assessment and registration instruments - were produced based on in-depth reading of the corpus, as well as dialogue with the theoretical framework elaborated for this research. Initially, the emergency context of the National Pact for Literacy at the Right Age - Pacto Nacional pela Alfabetização na Idade Certa (PNAIC) identifying its areas and structure of operation and the program training materials for the literacy teachers. In a second moment, the main theoretical perspectives on the assessment of learning produced in the last decades of the 20th century are approached and it seeks to discuss how the theme of the student's place in the evaluation process has been treated in the academic production of the area in Brazil. As results of the work we have that there are different theoretical and methodological perspectives to support the assessment in the literacy cycle in the PNAIC Notebooks (Cadernos do PNAIC), as well as the absence of a place to be occupied by the student in the evaluation process, although PNAIC adopts in its notebooks a conception of formative evaluation. We evidenced the control of teacher and student actions, mainly through regulating learning instruments of the established contents as a condition for the progression of children.